2020
DOI: 10.1126/sciadv.aay3499
|View full text |Cite
|
Sign up to set email alerts
|

Rebound of self-lubricating compound drops

Abstract: Drop impact on solid surfaces is encountered in numerous natural and technological processes. Although the impact of single-phase drops has been widely explored, the impact of compound drops has received little attention. Here, we demonstrate a self-lubrication mechanism for water-in-oil compound drops impacting on a solid surface. Unexpectedly, the core water drop rebounds from the surface below a threshold impact velocity, irrespective of the substrate wettability. This is interpreted as the result of lubric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 76 publications
2
32
1
Order By: Relevance
“…2b, by increasing the Weber number, the normalized impact time t i , defined as the time until the arrested droplet reaches the maximum out-of-plane height H max , slightly fluctuates but has distinct values for different overlayer viscosities, suggesting a prominent role played by the overlayer. Interestingly, it has been reported that the addition of the lubricant can actually promote rebound by masking droplet/ substrate pinning 37 , a result that seems contradictory to our observation. To reconcile the apparent conflict, we compare the impact outcomes of different overlayer viscosities in Supplementary Fig.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…2b, by increasing the Weber number, the normalized impact time t i , defined as the time until the arrested droplet reaches the maximum out-of-plane height H max , slightly fluctuates but has distinct values for different overlayer viscosities, suggesting a prominent role played by the overlayer. Interestingly, it has been reported that the addition of the lubricant can actually promote rebound by masking droplet/ substrate pinning 37 , a result that seems contradictory to our observation. To reconcile the apparent conflict, we compare the impact outcomes of different overlayer viscosities in Supplementary Fig.…”
Section: Resultscontrasting
confidence: 99%
“…Figure 2a shows the evolution of the normalized contact lengths D(t)/D 0 . Compared with pure water droplets, overlaid droplets take slightly longer to attain the maximum contact length, showing the influence of the overlayer on the impact, as described in previous studies [35][36][37] . In receding, D(t) of pure water decreases and returns to 0 upon rebound.…”
Section: Resultssupporting
confidence: 82%
“…The contact time τ of the bouncing droplet scales with the inertial‐capillary timescale τ 0 ∼ ( ρR 3 /γ) 1/2 , where ρ is the liquid density, R is the drop radius, and γ is the surface tension of the liquid, which is considered to be independent of the impact velocity but depends on the droplet radius. [ 40 ] Recently, Thoraval and co‐workers [ 41 ] reported that for the impact of water‐in‐oil compound droplets, water core unexpectedly rebounds below the threshold velocity independent of the surface wettabilities via the self‐lubricant of oil shell (Figure 3c).…”
Section: Impact Of Droplets On Solid Surfacesmentioning
confidence: 99%
“…Rebound, breakup: Reproduced with permission. [ 41 ] Copyright 2020, American Association for the Advancement of Science (AAAS). Splash, deposition: Reproduced with permission.…”
Section: Impact Of Droplets On Solid Surfacesmentioning
confidence: 99%
“…Compound drops, consisting of multiple immiscible fluids, are encountered in a wide range of industrial applications [1], such as drug encapsulation [2,3], food industry [4,5], combustion [6,7], and additive manufacturing of complex (bio)materials [8][9][10]. The impact of these compound drops produces a rich variety of dynamics [1,[11][12][13][14][15][16][17][18][19]. In the case of a coaxial water-in-oil compound drop impacting on a solid surface, Blanken et.al [17] discovered the emergence of a very thin and fast oil jet during the rebound of the water core for some impact parameters.…”
Section: Introductionmentioning
confidence: 99%